Vertical profiles of activated ClO and ozone loss in the Arctic vortex in January and March 2000: In-situ observations and model simulations - Vogel, B.; Stroh, F.; Grooß, J. U.; Müller, R.; Deshler, M. C.; Karhu, J.; McKenna, D. S.; Müller, M.; Toohey, D.; Toon, G. (Journal of Geophysical Research: Atmospheres, 2003)
[ 1] In situ observations of ClO mixing ratios obtained from a balloonborne instrument launched in Kiruna on 27 January 2000 and on 1 March 2000 are presented. ClO mixing ratios and quasi- simultaneously observed ozone loss are compared to model simulations performed with the Chemical Lagrangian Model of the Stratosphere ( CLaMS). ClO mixing ratios are simulated initializing the model simulations for early winter conditions. Sensitivity studies are performed to explore the impact of the surface area of the background aerosol, of denitrification, and of the recently reported kinetics of the ClO self- reaction [ Bloss et al., 2001] on simulated ClO. For 27 January 2000, model simulations agree with rate constants reported by Bloss et al. [ 2001], whereas for 1 March 2000 simulations employing rate constants reported by Bloss et al. [ 2001] and by Sander et al. [ 2000] reproduce the ClO measurements. The impact of uncertainties arising from accumulated errors along the calculated backward trajectories and uncertainties within temperatures derived from the UK Met Office are also studied. For both flights, simulated ClO show a good overall agreement with measured ClO within uncertainties arising from accumulated errors along air parcel histories. We find a layer of low ClO mixing ratios < 100 pptv between 600 and 620 K for the flight on 27 January 2000 and between 525 and 550 K on 1 March 2000. For this layer, measured ClO is substantially lower than simulated ClO. Potential causes are discussed, but the discrepancy remains unexplained at present. Furthermore, for 1 March 2000, an overall agreement is found between model simulations and measurements by the HALOE instrument of HCl and NOx (= NO + NO2) for all altitudes considered. We conclude that denitrification occurred up to a potential temperature of approximate to 550 K ( approximate to 24 km altitude) on 1 March 2000. Finally, model simulations show that between late January and 1 March, a significant ozone loss of about 0.8 - 1.8 ppmv is derived between 425 ...